Cover Picture: Steel Construction 3/2016. Issue 3 (August 2016) - Unknown
Abstract: Situated around 31 miles to the Southeast of Istanbul, the Izmit Bay Bridge is the suspension bridge with the 2 nd longest main span in the world. As the location is situated in one of the world's most active seismic zones, the bridge is designed to resist earthquakes of magnitude up to 8. MAURER successfully fulfilled the challenging task to design special expansion joints with fuse box, which in case of earthquakes shall accommodate movements of up to ± 3, 8 m, while remaining trafficable after the seismic event. (© MAURER, see pages A 4 – 5 of the May 2016 issue)